2022
DOI: 10.3390/ijms23158394
|View full text |Cite
|
Sign up to set email alerts
|

Light Spectral Composition Modifies Polyamine Metabolism in Young Wheat Plants

Abstract: Although light-emitting diode (LED) technology has extended the research on targeted photomorphogenic, physiological, and biochemical responses in plants, there is not enough direct information about how light affects polyamine metabolism. In this study, the effect of three spectral compositions (referred to by their most typical characteristic: blue, red, and the combination of blue and red [pink] lights) on polyamine metabolism was compared to those obtained under white light conditions at the same light int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Partly similar results were found in the present experiment, as SPM induced the synthesis of PUT and activated the expression of AtADC2 and AtSPMS but decreased that of the AtSPDS2. In wheat, it was also demonstrated that the effect of supplementary blue and far-red light was opposite on the PA metabolism-related gene expression in the leaves; in addition, PA treatment could partly reverse these differences [39]. Nevertheless, in the present study, we first demonstrated that the responses of wild-type and phyA mutant plants are partly different and depend on the light spectral conditions.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…Partly similar results were found in the present experiment, as SPM induced the synthesis of PUT and activated the expression of AtADC2 and AtSPMS but decreased that of the AtSPDS2. In wheat, it was also demonstrated that the effect of supplementary blue and far-red light was opposite on the PA metabolism-related gene expression in the leaves; in addition, PA treatment could partly reverse these differences [39]. Nevertheless, in the present study, we first demonstrated that the responses of wild-type and phyA mutant plants are partly different and depend on the light spectral conditions.…”
Section: Discussionmentioning
confidence: 45%
“…PA biosynthesis is controlled by light (light quality and quantity) [38,39], and on the other hand, PAs are able to influence photosynthesis in several ways (reviewed in [24]). PhyA is a unique photoreceptor responsible for the high far-red light irradiance response…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations